Komunikasi dalam Perencanaan Pembangunan: Suatu Kajian Kritis dalam Konteks Kebijakan Lingkungan dan Partisipasi Publik - Yusri, Nori; Wardi, Yunia; Evanita, Susi (Jurnal Salingka Nagari, 2025)
This study aims to explore the strategic role of communication in development planning, particularly within the framework of participatory and sustainable environmental policy. Employing a qualitative exploratory approach through literature review, this research analyzes recent studies (2021–2025) from diverse geographical contexts to identify patterns, challenges, and contributions of communication to the effectiveness of development policy. The findings indicate that two-way, deliberative, and context-sensitive communication enhances public participation, strengthens policy legitimacy, and bridges gaps between the state and civil society actors. Nevertheless, barriers such as power imbalances, weak institutional capacity, and social exclusion remain significant obstacles. The study underscores the need for policy communication designs that are not merely procedural but also substantive and transformative. These findings contribute theoretically to the discourse on development communication, while offering practical recommendations for planners, policymakers, and scholars in designing inclusive, responsive, and just communication systems for sustainable development governance.